Optimalisasi Pengelolaan Sampah melalui Pelatihan Biopori di Kelurahan Pisang Candi RW4, Kecamatan Sukun, Kota Malang: Optimalisasi Pengelolaan Sampah melalui Pelatihan Bioporidi Kelurahan Pisang Candi RW4, Kecamatan Sukun, Kota Malang - Karina Nathania Az Zahra; Anisa Fitria Ningrum; Muhammad Naufal Abdurrahman; Muhammad Taufik Hidayat; Zahra Nuriyatul Izzah; Nurul Mahmudah (Jurnal Pengabdian Masyarakat Kesehatan Terkini, 2026)
The accumulation of organic waste in RW 4, Pisang Candi Subdistrict, Malang City, has become an environmental issue that contributes to pollution and poses health risks to the community. To address this problem, a community service program was carried out with the aim of raising public awareness and tackling environmental issues through the management of organic waste by training residents in the creation of biopore infiltration pipes. The methods used included raising awareness about the health impacts of waste, educating the community on environment-related diseases, and conducting hands-on training in the production and installation of biopore pipes. The results showed an increased understanding among residents of the importance of waste management, along with strong enthusiasm for the training and application of biopore systems in their households. Biopore training has proven to be an effective model for sustainable community empowerment in organic waste management, supporting the creation of a cleaner, healthier, and more sustainable environment.